1978
DOI: 10.1128/aem.36.5.710-714.1978
|View full text |Cite
|
Sign up to set email alerts
|

Dry-heat destruction of lipopolysaccharide: dry-heat destruction kinetics

Abstract: Dry-heat destruction kinetics of lipopolysaccharides from Escherichia coli, Serratia marcescens, and Salmonella typhosa at 170 to 250 degrees C are described. The destruction rate seems to follow the second order and can be linearized by the equation, log y = a + b . -10cx. Because c is the slope, 1/c = D3. Both a and b are constant at a given temperature and are linear functions of temperature. The D(3)170, D(3)190, D(3)210, D(3)230, and D(3)250 values for E. coli lipopolysaccharide are 251, 99.4, 33.3, 12.3,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
39
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 25 publications
1
39
0
Order By: Relevance
“…The standard deviations of the slope and intercept were 0.002 C 21 and 0.203, respectively. The resulting Z value was calculated to be 20.9 6 0.7 C, which is consistent with other values reported in the literature 16,18,19 (Table 3). In the slow regime, the calculated rate constants departed from the expected Arrheniusbased temperature dependence observed in the fast regime in the temperature range examined.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…The standard deviations of the slope and intercept were 0.002 C 21 and 0.203, respectively. The resulting Z value was calculated to be 20.9 6 0.7 C, which is consistent with other values reported in the literature 16,18,19 (Table 3). In the slow regime, the calculated rate constants departed from the expected Arrheniusbased temperature dependence observed in the fast regime in the temperature range examined.…”
Section: Resultssupporting
confidence: 90%
“…These comparisons enabled accurate detection and quantification of a test sample's endotoxin content. Previous investigators have demonstrated that results obtained from the LAL assay results were consistent with pyrogen testing, 19,22 suggesting that this is a suitable method to quantify endotoxin inactivation from steam-heat treatment.…”
Section: Bacterial Endotoxins Testingmentioning
confidence: 69%
See 3 more Smart Citations